STRUKTURASI DALAM ORGANISASI SOSIAL (Studi Pada Forum Kerukunan Umat Beragama) - Rini Purwanti; Firman Kurniawan Sujono (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This study begins by questioning the performance of FKUB (forum for interreligious harmony) assigned as an agent of interreligious harmony in Indonesia. By using AST (Adaptive Structuration Theory), proposed by De Sanctis & Poole, the author looks at the social interaction between agent and structure in light of produced and reproduced structure. Through interviewing informants, this study found that the appropriation of structure is determined by the social interaction of the agents. Provided it is done faithfully according to the spirit of the structure, the decision outcome will be predictable. The resources will change and develop according to agent capacity. The resources that embedded in agent can become a safety valve for an organization. The implication will be for decision making, as the dynamics and complexity of interreligious harmony, every teamwork member should understand the process of structuration in the policy making whereby rules and resources are implemented so that members can participate actively, democratically and capably.